A study on energy (thermal) efficient aquaculture buildings for recirculating tank system / Sabarinah Sh Ahmad, Mohd Salleh Kamaruddin and Elias Salleh - Sh Ahmad, Sabarinah; Kamaruddin, Mohd Salleh; Salleh, Elias (Research Management Institute (RMI), 2011)
Malaysia plans to increase in its annual aquaculture production to 662,000 tons by year 2015 from the current 200,000 tons. Almost all of these culture systems release untreated effluents and wastes directly into the natural bodies especially coastal waters. This practice has resulted in many environmental problems. It has also affected the quality of culture water especially among the shrimp and marine fish (cage) farmers as the aquaculture effluents accumulated over the years deteriorate the quality of the surrounding waters which is the source of water input. An FAO study shows that upto 79% dietary N and 85% dietary P inputs in a fish cage culture system are lost into the surrounding waters. To sustain a healthy and environmental friendly aquaculture development in Malaysia, intensive recirculating tank systems have to be used. These systems are expected to become increasingly important especially in freshwater aquaculture where the industry has to compete for limited water resource with other agricultural activities, industrial and domestic users. The Ministry of Agriculture and Agro-based Industries (MoA) have started pilot projects in Kedah, Sarawak and Selangor. At present, all recirculating tank systems have to be housed in enclosed buildings. These buildings are designed for temperate and cold climates with its main concern to ward off cold temperature from entering the building while maintaining the inside warm temperature. Buildings designed for temperate and cold climates are not suitable for tropical environments and are thermally uncomfortable (and may become too hot if kept enclosed) for Malaysians. The proposed study is undertaken: a. to measure the environmental conditions of selected buildings that house recirculating tank Systems b. to develop suitable designs for aquaculture buildings for tropical environments. No such study has been done for the hot humid tropical climate and very few studies have been conducted on the designs of the aquaculture buildings for the temperate and cold conditions